STUDIES ON PROTEIN AND CARBOHYDRATE ACCUMULATION PATTERN AS INFLUENCED BY PRODUCTION PRACTICES IN CHICKPEA - SHILPA, - (Annals of Agricultural Research, 2014)
In an experiment the protein and carbohydrate content of chickpea was studied in samples collected for 2 years in 8 locations. The content of both protein and carbohydrate differed significantly due to locations, production practices viz. rainfed and irrigated, and time of sowing. The content varied within a range among different locations. The protein content was higher in irrigated production. The timely sown chickpea showed higher protein content compared to late sown, while no such differences were observed in irrigated production.